2001
DOI: 10.1038/eye.2001.165
|View full text |Cite
|
Sign up to set email alerts
|

Indocyanine green augmented transpupillary thermotherapy in the management of choroidal metastasis from breast carcinoma

Abstract: Indocyanine green augmented transpupillary thermotherapy is a viable alternative for management of solitary choroidal metastasis from breast carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 8 publications
1
14
0
Order By: Relevance
“…5,6 The treatment modalities are versatile, but the effects are not impressive. The metastatic choroidal tumor presents as a yellowish, elevated, diffuse lesion with irregular borders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 The treatment modalities are versatile, but the effects are not impressive. The metastatic choroidal tumor presents as a yellowish, elevated, diffuse lesion with irregular borders.…”
Section: Discussionmentioning
confidence: 99%
“…The metastatic choroidal tumor presents as a yellowish, elevated, diffuse lesion with irregular borders. 1,5,6 Hyperthermia is the elevation of body temperature above the normal of 37°C. Treatment is usually recommended if the tumor appears active and threatens vision despite concomitant systemic chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Puri et al reported the use of ICG-augmented transpupillary thermotherapy in the management of choroidal metastasis from breast carcinoma [20]. The investigators concluded that the combination of ICG and TTT was promising for the management of small, potentially sightthreatening choroidal metastasis [20].…”
Section: Discussionmentioning
confidence: 99%
“…The investigators concluded that the combination of ICG and TTT was promising for the management of small, potentially sightthreatening choroidal metastasis [20]. Costa et al used ICG as a photosensitizer in an experimental study on photodynamic therapy [25], and in the treatment of occult subfoveal choroidal neovascularization caused by agerelated macular degeneration [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation